Regulation of Hemoglobin Synthesis in a Murine Erythroblastic Leukemic Cell: The Requirement for Replication to Induce Hemoglobin Synthesis - McClintock, Patrick R. (1974)
The induction of hemoglobin synthesis by dimethylsulfoxide in cells infected with Friend leukemia virus has been shown to depend on the number of cell divisions after the addition of the inducing agent. In asynchronous cultures the cells have a generation time of 24 hr, and hemoglobin synthesis occurs after 48 hr in the presence of dimethylsulfoxide. Generation times were extended by lowering the serum content of the medium. In 7.5% and 2.5% fetal calf serum, the generation time was increased to 36 hr and 48 hr, respectively, and hemoglobin synthesis began at 72 hr and 96 hr, respectively. In the presence of N(6),O(2)′-dibutyryladenosine 3′:5′-cyclic monophosphate the generation time was extended to 38 hr, and hemoglobin synthesis began after 72 hr in dimethylsulfoxide. The number of cell doublings, under conditions where the generation time was 24 hr, was regulated by the size of the initial cell concentration. When a low inoculum (1.5 × 10(5) cells per cm(3)) was used, the culture was still in log phase after two doublings and hemoglobin appeared in log phase; a moderate initial inoculum (4.2 × 10(5) cells per cm(3)) took the culture into stationary phase after two doublings, and hemoglobin synthesis was induced in stationary-phase cells. Heavy inocula (3.7 × 10(6) cells per cm(3)) maintained the cells in stationary phase, and under these conditions no induction of hemoglobin synthesis occured. We conclude from these studies that the initiation of hemoglobin synthesis required two rounds of mitosis after treatment with dimethylsulfoxide. In studies with synchronized cultures of cells infected with Friend leukemia virus, two mitoses were required for the initiation of hemoglobin synthesis. We conclude that two rounds of DNA synthesis and/or mitosis are also required for the dimethylsulfoxide-mediated induction of erythroid differentiation and hemoglobin synthesis in these cells.